Investing in hospitals of the future - Rechel, Bernd; Wright, Stephen; Edwards, Nigel; Dowdeswell, Barrie; McKee, Martin (World Health Organization, European Observatory on Health Systems and Policies, 2009)
Collected works which focus on the process of planning of investments in hospitals. Intended for the professional public.
Observatory studies series ; No. 16
Keywords: Hospitals; Healthcare Financing; podnikání; kapitálové financování; management, organizace a řízení zdravotnictví; Investments; Entrepreneurship; ekonomie, ekonomika, ekonomika zdravotnictví; nemocnice; Capital Financing; financování zdravotní péče; investice